2019
DOI: 10.1177/0278364919840415
|View full text |Cite
|
Sign up to set email alerts
|

A variable admittance control strategy for stable physical human–robot interaction

Abstract: Admittance control allows a desired dynamic behavior to be reproduced on a non-backdrivable manipulator and it has been widely used for interaction control and, in particular, for human–robot collaboration. Nevertheless, stability problems arise when the environment (e.g. the human) the robot is interacting with becomes too stiff. In this paper, we investigate the stability issues related to a change of stiffness of the human arm during the interaction with an admittance-controlled robot. We propose a novel me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 37 publications
0
68
0
Order By: Relevance
“…Additionally, they have experimentally shown that increasing admittance mass as well as damping contributes to the stability of the system, when instability is detected [7]. Recently, Ferraguti et al proposed an improved heuristic method for detecting the emergence of instability and a passivity-preserving inertia adaptation strategy with the use of energy tanks concept [17].…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they have experimentally shown that increasing admittance mass as well as damping contributes to the stability of the system, when instability is detected [7]. Recently, Ferraguti et al proposed an improved heuristic method for detecting the emergence of instability and a passivity-preserving inertia adaptation strategy with the use of energy tanks concept [17].…”
Section: A Related Workmentioning
confidence: 99%
“…Earlier studies in pHRI have relied on increasing the damping of the controller to increase the stability robustness of a system through energy dissipation. Some alternative approaches adapt the mass and/or the ratio between mass and damping of the controller [7], [15]- [17]. Making such alterations in the controller parameters are shown to be promising and result in better responses than an LTI interaction controller with fixed parameters.…”
Section: B Contributionsmentioning
confidence: 99%
“…The method proposed in Piwowarczyk et al ( 2020 ) uses an admittance controller to scale the force applied by the user on the robot in relation to force applied to the environment. The stability of admittance-controlled robots and their ability to cope with different environmental forces have been investigated in Ferraguti et al ( 2019 ). Admittance control was used in Li et al ( 2018 ) for an exoskeleton robot to create a reference trajectory based on measured force.…”
Section: Prior Workmentioning
confidence: 99%
“…In [19] the wave variable transformation was exploited to modulate the energy and improve the transparency of a teleoperation system. Regarding the energy tank, [20] proposes an impedance control with time-varying stiffness to guarantee system passivity. For admittance controlled robots, [21] exploits the tank for controlling a robotic arm for surgical application and [22] extends the method considering interactions with the environment.…”
Section: Introductionmentioning
confidence: 99%